Matrine family derivatives: Synthesis, reactions procedures, mechanism, and application in medicinal, agricultural, and materials chemistry - Jamal A.H. Kowah; Ruobing Gao; Fu Li; Chenxi Guang; Meiyan Jiang; Xiaolin Wu; Lisheng Wang; Xu Liu (European Journal of Medicinal Chemistry Reports, 2023)
Matrine alkaloid is a type of Sophora flavescens (Ku Shen) found in plants. It holds excellent applications for anticancer, antimicrobials, antibacterial, anti pests, and other applications in material chemistry such as electrochemical. Owing to its superior biological and pharmaceutical properties over the past decade, pharmaceutical researchers have demonstrated that matrine can defeat the proliferation of various cancer cells, such as the proliferation of the human erythroleukemia cell line K562 and human hepatic cancer cell line SMMC-7721. This review mainly highlights the recent progress of matrine in synthesis, reaction procedures, mechanisms, and applications in medicinal, agricultural, and materials chemistry. In addition, we have also paid attention to the reactivity of matrine rings with different positions, including reactivity in N-1, C-13, C-14, (A, B, C) rings, carbonyl group at 15 positions, and amide bond at 15 and 16 positions, fused D-ring, opened A, B, and D-ring, via structural simplification, and total synthesis and design of matrine analogues from other compounds with different strategies. Particularly, the reported strategies were conducted in classical and non-classical conditions, mainly green conditions such as green solvents, catalysts, and other procedures.